Mono- and dinuclear palladium(II) compounds containing N,S donor ligands - Synthesis, characterization and thermal behavior - Moro, A. C.; Mauro, A. E.; Ananias, S. R.; Stevanato, A.; Legendre, A. O. (Springer, 2007)
Synthesis, spectroscopic characterization and thermal analysis of the compounds [Pd-2(dmba)(2)(mu-NCO)(mu-2-qnS)] (1), [Pd-2(dmba)(2)(mu-NCO)(mu-8-qnS)] (2), [Pd(2-qnS)(2)] (3) and [Pd(8-qn(S))2] (4) (dmba=N,N-dimethylbenzylamine; 2-qnS=2-quinolinethiolate; 8-qnS=8-quinolinethiolate) are described. The thermal decomposition of these compounds occurs in four consecutive steps and the final decomposition products were identified as Pd(0) by X-ray powder diffraction. The thermal stability order of the complexes is 4 > 3 > 1 > 2.
Keywords: chelates; cyclopalladated compounds; quinolinethiol; thermal analysis